Identification of Potential Mantle Rocks Around the Lunar Imbrium Basin. Issue 22 (23rd November 2020) - Bretzfelder, Jordan M.; Klima, Rachel L.; Greenhagen, Benjamin T.; Buczkowski, Debra L.; Petro, Noah E.; Day, Mackenzie
Abstract: Basin‐forming impacts expose material from deep within the interior of the Moon. Given the number of lunar basins, one would expect to find samples of the lunar mantle among those returned by the Apollo or Luna missions or within the lunar meteorite collection. However, only a few candidate mantle samples have been identified. Some remotely detected locations have been postulated to contain mantle‐derived material, but none are mineralogically consistent upon study with multiple techniques. To locate potential remnants of the lunar mantle, we searched for early‐crystallizing minerals using data from the Moon Mineralogy Mapper (M 3 ) and the Diviner Lunar Radiometer (Diviner). While the lunar crust is largely composed of plagioclase, the mantle should contain almost none. M 3 spectra were used to identify massifs bearing mafic minerals and Diviner was used to constrain the relative abundance of plagioclase. Of the sites analyzed, only Mons Wolff was found to potentially contain mantle material. Plain Language Summary: During the Moon's early development, minerals such as olivine and pyroxene would have crystallized first, sinking toward the lunar interior and becoming the primary components of the mantle. After approximately 70–80% of the magma ocean solidified, plagioclase began to crystallize and floated on the iron‐rich residual melt. The lunar highland crust is characterized by an abundance of plagioclase, whereas samples of the mantle should contain very little plagioclase. Considering the size and number of large impact basins on the Moon, one would expect that some of these dug through the lunar crust, exposing lunar mantle. However, very few candidates for mantle material have been identified among the lunar samples on Earth. This study uses near‐infrared data from the Moon Mineralogy Mapper to identify sites on the surface that contain early‐crystallizing minerals (olivine and pyroxene), which are indicative of mantle material. These sites were then analyzed using data from the Diviner Lunar Radiometer, which is able to constrain the abundance of these minerals relative to the amount of plagioclase present. Based on our analysis, the Imbrium Basin contains only one instance of rocks that are mineralogically consistent with being sourced from the mantle. Key Points: Lunar rocks exhibiting mafic signatures in the near infrared are inconsistent with ultramafic compositions when viewed in the mid‐infrared Combining data from the Moon Mineralogy Mapper and Diviner Lunar Radiometer enabled bulk and mafic mineralogy to be robustly interpreted A near‐ and mid‐infrared survey of the inner and outer rings of Imbrium Basin reveals only Mons Wolff as potential exposed mantle